Household Organic Waste Processing to Produce Eco Enzym at Kartosuro Christian Protestant Church (Gkpo), Sukoharjo, Central Java, Indonesia - Cicik Sudaryantiningsih; Yonathan Suryo Pambudi; Widianto; Agerippa Yanuranda Krismani; Richardus Indra Gunawan; Elvis Umbu Lolo (Asian Journal of Community Services, 2023)
In counseling in the form of community service for the Oikumene Protestant Christian Church (GKPO) Kartosuro which was carried out by a lecturer in the Environmental Engineering Study Program, Faculty of Engineering, Christian University of Technology Solo regarding the use of organic waste to produce eco enzymes, giving hope and benefits about utilizing good and sustainable organic waste. Processing organic waste from home also contributes to mothers in their respective households each to support the local government program of Sukoharjo Regency in controlling waste generation and producing eco enzyme products that directly benefit their respective families. The result of this community service activity is that PA GKPO Kartosura mothers received information on how to process organic waste into eco enzyme.